REDEFINISI HILÄ€L DALAM PERSPEKTIF FIKIH DAN ASTRONOMI - Putri, Hasna Tuddar (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2012)
Unification of the Islamic calendar was much needed and is a major requirement for Muslims today in the running of worship. Uniformity in to worship and celebrate Islamic holy days is something that has been long awaited. An expectation of the Islamic calendar is determining who has the certainty that a better and more organized for various purposes. However, it is in conflict with a different concept of the new moon from several groups paradigm respectively, both from the perspec tive of science and religion. HilÄl is one of the main sources in the preparation of the I slamic calendar. Currently, the definition of the new moon is very diverse. Which d efinition is used for the initial determination new month of hijriyah, both from the perspective of astronomy or fiqh, or combination of them. Therefore, the article is devoted to the redefinition of the concept of the new moon from the perspective of science and fiqh, that synergy occurs between fiqh and the astronomical new moon to determine new month of Islam. So that the unity of the Islamic calendar can be realized well.***Penyatuan kalender Islam sangat dibutuhkan dan merupakan syarat utama bagi umat Islam saat ini dalam menjalankan ibadah. Keseragama n dalam beribadah dan merayakan hari besar Islam adalah sesuatu yang telah lama ditunggu. Harapan atas kalender Islam adalah sebuah kalender yang memilikikepastian (akurasi) lebih baik dan lebih terorganisir untuk berbagai keperluan. Namun dalam realitas terdapat perbedaan pandangan tentang konsep bulan baru oleh beberapa kelompok, baik dari perspektif ilmu pengetahuan maupun agama. HilÄl adalah salah satu sumber utama dalam penyusunan kalender Islam. Saat ini definisi bulan baru sangat beragam, padahal definisi inilah yang digunakan untuk penentuan awal bulan ba ru Hijriyah, baik dari sudut pandang fikih astronomi atau kombinasi dari mereka. Artikel ini difokuskan untuk mendefinisikan kembali konsep bulan baru dari sudut pandang ilmu pengetahuan (astronomi) dan fikih. Sinergi antara fikih dan ast ronomi sebagai pendekatan untuk menentukan bulan baru Islam perlu diupayakan sebagai sebuah ikhtiar untuk merumuskan kesatuan kalender Islam.***Keywords: kalender HIjriyah, hilÄl , astronomi, fikih